THE REFLECTIONS OF SEXISM AND FEMINISM IN GOCE SMILEVSKI’S NOVEL CALLED FREUD’S SISTER - Arzu ÖZYÖN (Fırat University, 2021)
This study, generally aims to reveal the attitude towards women in the patriarchal society in the 19th century Europe through Goce Smilevski’s novel called Freud’s Sister, once again. In particular, on the axis of attitude towards women, feminism versus sexism and the concept of madness versus normality will be handled. In the study, where naturally feminist theory will be adopted, classical works like Virginia Woolf’s A Room of One’s Own and Susan Gubar and Sandra Gilbert’s The Madwoman In The Attic, which never become old-fashioned despite the long years that passed and which still harbour up-to-date ideas, will be used as secondary sources. As a result, it will be put forth that despite some changes, the extensions of the stereotype of Victorian woman also continues to exist in the 19th century; sexism keeps a firm place in the society visibly, and sometimes it is even expressed directly; despite that on the side of women, some developments are observed in terms of Women’s Movement or feminism but these are minor developments which are not enough, therefore the women who do not conform to the norms of the society and the roles that were shaped for them by the patriarchal society, are accepted as “not normal” or “mad” and this social order has not changed much (here the time in the novel is meant) since the Victorian period and the attitude towards women in the patriarchal society still continues in the 19th century as it did in that era.